Abnormal resting-state connectivity of motor and cognitive networks in early manifest Huntington's disease - Wolf, Robert Christian; Depping, Malte S.; Thomann, Philipp (Psychological medicine, 2014)
Background. Functional magnetic resonance imaging (fMRI) of multiple neural networks during the brain’s ‘resting state’ could facilitate biomarker development in patients with Huntington’s disease (HD) and may provide new insights into the relationship between neural dysfunction and clinical symptoms. To date, however, very few studies have examined the functional integrity of multiple resting state networks (RSNs) in manifest HD, and even less is known about whether concomitant brain atrophy affects neural activity in patients. - Method. Using MRI, we investigated brain structure and RSN function in patients with early HD (n = 20) and healthy controls (n = 20). For resting-state fMRI data a group-independent component analysis identiﬁed spatiotemporally distinct patterns of motor and prefrontal RSNs of interest. We used voxel-based morphometry to assess regional brain atrophy, and ‘biological parametric mapping’ analyses to investigate the impact of atrophy on neural activity. - Results. Compared with controls, patients showed connectivity changes within distinct neural systems including lateral prefrontal, supplementary motor, thalamic, cingulate, temporal and parietal regions. In patients, supplementary motor area and cingulate cortex connectivity indices were associated with measures of motor function, whereas lateral prefrontal connectivity was associated with cognition. - Conclusions. This study provides evidence for aberrant connectivity of RSNs associated with motor function and cognition in early manifest HD when controlling for brain atrophy. This suggests clinically relevant changes of RSN activity in the presence of HD-associated cortical and subcortical structural abnormalities.